The Diversity of Arbuscular Mycorrhiza Fungus (AMF) Indigenous in Peanuts (Arachis Hypogea L) Rhizosphere under Different Elevation - Surya Marizal; . Muzakir; Amaliah Syariyah (UNIVERSITY OF LAMPUNG, 2016)
Arbuscular Mycorrhiza Fungus (AMF) is a type of soil microorganisms with obligate symbiotic characteristic. It can associate with high-level plants at the rate of 90%. Its association level highly depends on the type of AMF and the host plant. The lack of information about the AMF diversity in an ecosystem, and the insufficient number and types of isolates available, are limiting factors for the widespread use of AMF. It was a survey and observation research. In this research AMF indigenous potentials were observed in soil and roots of peanuts. Samples were taken from area with different elevation: low, medium, and high in West Sumatra. The study reveals that the highest number of AMF indigenous spores in peanuts rhizosphere from area with different elevation: low, medium, and high are dominated by Glomus sp 1 (159 spores), Acaulospora sp1 (110 spora) and Glomus sp2 (82 spores), however AMF indigenous with the highest percentage of existence is Glomus sp1 and Acaulospora sp1 (100%). In addition, the infectious level of AMF indigenous on roots of peanuts are 81.1%, 64,4% and 78,9% on low, medium and high elevation, respectively. The highest number of population and infectious level are on low elevation whereas the lowest number is on high elevation. Thus, the elevation level correlates with the type of infection, the size of population, and the percentage of infection.